Computerization as a component of informational education - Дрогайцев, Олександр Іванович (Pedagogy of Higher and Secondary Education, 2013)
Drogaytsev O. I. Computerization as a component of informational education. The article considers the issue of computerization of the educational process in modern schooling. Computer education is understood as a dynamic process, the main trends of its development are associated with the expansion of computer usage in the educational process. The didactic possibilities of the Internet are revealed.